The World Energy Book : An A-Z atlas and Statistical Source Book - Crabbe, David; McBride, Richard (London : Kogan Page, 1978)
The World Energy Book is intended as a comprehensive reference guide to energy sources, energy related terminology, economics, and all factors related to the search for, extraction of, production and utilization of the major and alternative sources of energy. There are three main sections of the book, an A-Z containing some 1000 terms and definitions, the Energy Atlas and the Statistical Data Section.
ne 16/04/2018
Loan
Keywords: Energy Policy; Power Resources